Designing and validating an adaptation tool for endometriosis: an exploratory mixed method study protocol - Sanaz Mollazadeh; Nahid Marvi; Talat Khadivzadeh (Reproductive Health)
Abstract Background Endometriosis is a benign and chronic gynecological estrogen-dependent condition. Research findings have highlighted its impact on different aspects of women's lives. Enhancing quality of life and supporting the well-being of those affected is advised. Yet, none of the conducted studies have taken action toward these objectives. Therefore, the present study will be conducted with the aim of "Designing adaptation tool for endometriosis". Methods/design The method used in this study is an exploratory mixed-method study. The study will consist of two phases, starting with a qualitative phase followed by a quantitative phase. Upon approval Ethics Code from the endometriosis clinic at Imam Reza Hospital in Mashhad, Iran. The research will involve women of reproductive age diagnosed with endometriosis. In-depth and semi-structured interviews with open-ended questions will be conducted. The research aims to explore the experiences of women with endometriosis in adapting to the condition, utilizing qualitative content analysis with an approach based on the "ROY adaptation model." Sampling will be purposive until data saturation is achieved. Data analysis will follow the suggested steps using Elo Kingas' method and MAXQDA20 software. Tool design will involve an inductive approach (informed by qualitative findings) and a comparative method (based on literature review) to develop and refine tool items. Discussion This study is the first to employ a mixed-method approach in developing an adaptation tool for endometriosis. It uncovers underlying issues in the attitudes of patients, medical staff, and healthcare providers, offering insight into factors that can enhance the health and quality of life of affected women. The research findings can inform the creation of a relevant strategy for policymakers, planners, and healthcare professionals to better address the needs of women impacted by endometriosis. Ethical code: IR.MUMS.NURSE.REC.1403.069.